Implementasi Subjek, Objek dan Tarif Pajak pada Kegiatan Keolahragaan di Kota Mojokerto - Andhiyan Mergining Mei, Nanang (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The high public awareness regarding sports has received a positive response from the government and from the private sector. The response was in the form of providing funds for sports activities. Sports activities with the use of financial budgets are of course closely related to taxation. Taxes are people's contributions to the state treasury based on laws that can be enforced by not receiving direct services in return that can be shown and used to pay public expenses. Discussions on taxes will be related to the subject, object and tax rate. The close relationship between sports activities and taxes means that there must be clarity as to who is the subject and object of sports activities and the amount of tax rates imposed.